Humanitarianisme Soedjatmoko : visi kemanusiaan kontemporer - Masruri, Siswanto, 1953-; Heryawan, Lukman (Yogyakarta : Pilar Media, 2005)
Analyzing the thoughts of Soedjatmoko on humanitarianism and his contribution on human welfare in Indonesia
Includes bibliographical references (p. 365-385) and index
Keywords: Soedjatmoko, -- 1922-189; Humanitarianism -- Indonesia; Humanitarian assestance; Humanitarianism -- Religions aspects; Humanitarianism -- Political aspects